2019
DOI: 10.1016/j.tjem.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Association of optic nerve sheath diameter in ocular ultrasound with prognosis in patients presenting with acute stroke symptoms

Abstract: BackgroundMeasurement of optic nerve sheath diameter (ONSD) by means of ocular ultrasound (US), can diagnose elevated intracranial pressure (ICP). Stroke accompanied by elevated ICP might have a worse prognosis.ObjectiveTo determine the relationship of ONSD in ocular US with prognosis in acute stroke in the emergency department (ED).MethodsPatients with acute presentations of stroke, presenting to the ED in 2017 (during six months), were enrolled in our study. US exam was performed on all of them and ONSD was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Therefore, ONSD measurement is a non-invasive and reliable method used to estimate increased ICP. Although ultrasonography is more frequently preferred for ONSD measurement, there are many studies in which ONSD measurement is performed in CT and magnetic resonance imaging [4,5,[17][18][19]. Head CT is often requested to exclude structural lesions in patients presented to the ED with HE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ONSD measurement is a non-invasive and reliable method used to estimate increased ICP. Although ultrasonography is more frequently preferred for ONSD measurement, there are many studies in which ONSD measurement is performed in CT and magnetic resonance imaging [4,5,[17][18][19]. Head CT is often requested to exclude structural lesions in patients presented to the ED with HE.…”
Section: Discussionmentioning
confidence: 99%
“…In cases that involve an increase in intracranial pressure (ICP), the subarachnoid area and retrobulbar segments are affected and the optic nerve sheath diameter (ONSD) increases [2]. It has been shown that there is a positive correlation between ONSD and an increase in ICP, however, most of these studies have examined structural etiologies of increased ICP such as intracranial edema, intracranial hemorrhage, and ischemic cerebrovascular accident [2][3][4][5]. On the other hand, an increase in ICP is also seen in a metabolic coma, such as hypertensive encephalopathy, diabetic ketoacidosis, and HE [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they observed that ONSD returned to pre-infusion values after the experiment. Hansen et al attempted to determine m. natIle et al 108,109), some types of meningitis (110,111), and stroke (112)(113)(114)(115). Hemorrhagic strokes are particularly common because aneurysmal SAH can cause irreversible distention of ONS, as discussed before.…”
Section: Onsd Variation and Relationship With Icpmentioning
confidence: 99%
“…At the same time, with an increase in ICP, brain hypoxia and secondary brain injury may occur, aggravating the patient's condition. The patient may have symptoms such as headache, drowsiness, coma, and even brain hernia, which will have a negative impact on neurological prognosis (Seyedhosseini et al, 2019;Lee et al, 2020b). Monitoring changes in ICP over time is very important for the treatment and prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ultrasonic measurement of optic nerve sheath diameter (ONSD) has attracted increasing attention as a new non-invasive repeatable method for estimating ICP (Zhang et al, 2017;Seyedhosseini et al, 2019). The optic nerve is ensheathed by three layers of meninges (the dura, arachnoid, and pia meninga), collectively known as the optic sheath.…”
Section: Introductionmentioning
confidence: 99%